THE EFFECT OF EARNINGS PER SHARE (EPS) & RETURN ON EQUITY (ROE) ON STOCK PRICE OF BANKING COMPANY LISTED IN INDONESIA STOCK EXCHANGE (IDX) 2010-2014 - Talamati, Mohamad Rianto; Pangemanan, Sifrid S (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Capital market is one of the instruments in the world of business to make profit. Investors invest at capital markets because of the expected profit. Investors often suffer loss of funds when investing because they do not see the factors that affect the value of the stock price. The purpose of this research was analyzing the effect of Earnings per Share (EPS) and Return on Equity (ROE) on Stock Price of banking company listed on Indonesia Stock Exchange in 2010-2014. The samples used were 5 banking companies that passed the test of purposive sampling. Correlation coefficient (R) indicates the variable has a strong relationship. Coefficient of determination shows that the Stock Price is influenced by the EPS and ROE. Simultaneously both EPS and ROE variables affect stock price. Partially, EPS have significant positive effect on Stock Price while ROE does not affect partially on Stock Price. Thus, banking companies listed in the Indonesia Stock Exchange in improving corporate performance need to pay attention to Earnings per Share and Return on Equity because both variables simultaneously have a significant effect on stock prices Keywords: stock price, EPS, ROE